FGN 47 Neurospora Bibliography - Craig Wilson (Fungal Genetics Reports, 2000)
This bibliography represents my attempt to collect all works dealing substantially with Neurospora. Please let me know of anything published in 1999 or 2000 that is not included here, so that it might be mentioned in the next bibliography.